2004
DOI: 10.1016/j.icvts.2004.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Does off-pump coronary artery surgery reduce the incidence of postoperative atrial fibrillation?

Abstract: A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was whether off-pump coronary artery surgery reduces the incidence of postoperative atrial fibrillation. Altogether 107 papers were found using the reported search, of which 18 presented the best evidence to answer the clinical question. The author, journal, date and country of publication, patient group studied, study type, relevant outcomes, results, and study weaknesses of these papers are tabulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
(12 reference statements)
0
7
0
1
Order By: Relevance
“…1,13,32 But the mechanisms underlying remains unknown and are thought to be multifactorial. Recently there are reports which demonstrate the role of inflammation in the initiation of AF, especially in postoperative AF following cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,13,32 But the mechanisms underlying remains unknown and are thought to be multifactorial. Recently there are reports which demonstrate the role of inflammation in the initiation of AF, especially in postoperative AF following cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergoing cardiac operations are more likely to develop AF during their postoperative period with the incidence ranging from 25% to 50%. 1 Moreover, recent studies have shown that postoperative AF is associated with increased morbidity and prolonged hospitalization, which requires additional medical and nursing time, even intensive care unit stay.…”
Section: Introductionmentioning
confidence: 99%
“…Off-pump coronary artery bypass reduces the incidence of postoperative AF compared with CABG on CPB. 73,100,102,[133][134][135] This is probably secondary to the blunted systemic infl ammatory response, avoidance of atrial cannulation, and reduced myocardial ischemia in OPCAB.…”
Section: Impact On Myocardial Functionmentioning
confidence: 99%
“…La cirugía coronaria sin CEC reduce, aunque no suprime, los valores circulantes de mediadores inflamatorios 74 , y la eliminación del pinzamiento aórtico reduce el sufrimiento miocárdico. Aunque los resultados clínicos no han alcanzado aún evidencia clase I, los resultados de series amplias observacionales indican el beneficio de esta técnica en términos de supervivencia a corto y largo plazo, principalmente en pacientes con disfunción ventricular, diabéticos y ancianos [79][80][81] , incidencia de infarto de miocardio y accidente cerebrovascular 82 , y reducción de la incidencia de fibrilación auricular postoperatoria 83 . La cirugía coronaria con injertos arteriales sin CEC asociada a anestesia epidural torácica y fast track representa actualmente el patrón oro.…”
Section: Cirugía Coronaria Menos Invasivaunclassified